Mekanisme Pemakzulan Presiden Sebelum Dan Sesudah Terbentuknya Mahkamah Konstitusi Di Indonesia - Rohmah, Elva Imeldatur; Dewi Kartika Sari (Fakultas Syariah Univeritas Islam Madura, 2022)
Indonesia is a republic in which the presence of a president is very crucial. From nomination until he takes office, a President must have characteristics and actions that reflect the contents of the law. If a President during his tenure is proven to have violated the provisions of the law, then the President can be impeached in various ways that have been regulated in the law. In the history of the Indonesian state administration, there have been impeachment of the President which was carried out without proof through the Constitutional Court. Because at that time the Constitutional Court had not yet been formed. Impeachment carried out on the basis of political judgment alone. In contrast, after the Constitutional Court was formed, the indictment against the President must first be proven in the Constitutional Court. This research is normative legal research, using a statute approach and a historical approach. The research sources come from primary legal materials consisting of the 1945 Constitution of the Republic of Indonesia and Law no. 24 of 2003 concerning the Constitutional Court. Secondary legal materials consist of books, journals, articles related to the research theme. The results showed that there were differences in the ratio legis used in impeaching the President before and after the establishment of the Constitutional Court. Before the Constitutional Court was formed, the legislative ratio used was based on Article 4 of the Decree of the MPR RI No. III/MPR/1978. Meanwhile, after the Constitutional Court was formed, the ratio legis used was Article 7A of the 1945 Constitution. The mechanism for impeachment was different between before and after the Constitutional Court was formed. Impeachment before the Constitutional Court was formed was based solely on political judgments. However, after the Constitutional Court was formed, impeachment was not only based on political judgment factors, but had to be judicially tested by the Constitutional Court.